A Review on Nematophagus Fungi: A Potential Nematicide for the Biocontrol of Nematodes - Lawal, Ibrahim; Fardami, Aminu Yusuf; Ahmad, Fatima Isma’il; Yahaya, Sani; Abubakar, Abdullahi Sani; Sa’id, Muhammad Abdullahi; Marwana, Musa; Maiyadi, Kamilu Adamu (Journal of Environmental Bioremediation and Toxicology, 2022)
Filamentous fungi offer an interesting biocontrol alternative. Trichoderma, mycorrhizal, and endophytic fungi are the main filamentous fungi used to induce nematode resistance. They can reduce plant-parasitic nematode damage by producing lytic enzymes, antibiosis, paralysis, and parasitism. They minimize space and resource competition by increasing nutrient and water uptake, or by modifying root morphology and/or rhizosphere interactions, which benefits plant growth. Filamentous fungi can induce nematode resistance by activating hormone-mediated plant-defense mechanisms (salicylic and jasmonic acid, strigolactones). Altering the transport of chemical defense components or the synthesis of secondary metabolites and enzymes can also boost plant defenses. Using filamentous fungi as BCAs against plant-parasitic nematodes is a promising biocontrol strategy in agriculture. By increasing a plant's ability to absorb nutrients and water, or by changing root shape and/or rhizosphere interactions, they reduce competition for space and resources. Filamentous fungi can activate hormone-mediated plant defenses (e.g., strigolactones, salicylic and jasmonic acids). Changing how chemical defense components are transported or synthesizing secondary metabolites and enzymes can improve a plant's defenses. Using filamentous fungi as BCAs in agriculture is a promising, long-lasting biocontrol method against plant-parasitic nematodes.